Keabsahan Clickwrap Agreement dalam Perspektif Asas Kebebasan Berkontrak di Indonesia - Santoso, Steven Surya; Suraji, Suraji (Indonesian Journal of Social Sciences and Humanities, 2026)
Advances in information technology have driven the use of electronic contracts, one of which is the clickwrap agreement, which is widely used in modern digital transactions. However, this form of agreement raises legal issues regarding its validity and the application of the principle of freedom of contract, particularly due to its inherently one-sided nature and limited room for negotiation. This study aims to analyze the validity of clickwrap agreements from the perspective of the principle of freedom of contract and to examine the challenges and implications within Indonesian contract law. The research method employed is normative legal research using a legislative and conceptual approach. Legal materials were collected through literature review and analyzed using the syllogistic method with deductive reasoning. The results of the study indicate that clickwrap agreements are valid and meet the requirements for a valid contract under Article 1320 of the Civil Code. However, the application of the principle of freedom of contract has not been optimal due to the lack of room for negotiation for users. The challenges that arise include an imbalance of power between the parties, a lack of user understanding of the contract’s contents, the potential for clauses that are detrimental to users, and regulatory ambiguity. The implications of these conditions relate to legal certainty, the status of the parties, consumer protection, law enforcement, and the development of contract law.